Are industry financial ties associated with greater scholarly impact among academic otolaryngologists?. (26th April 2016) - Svider, Peter F.; Bobian, Michael; Lin, Ho‐Sheng; Setzen, Michael; Baredes, Soly; Eloy, Jean Anderson; Folbe, Adam J.
Abstract : Objectives/Hypothesis: In response to concerns regarding physician–industry relationships, the Physician Sunshine Act of 2010 was passed in an effort to increase transparency and accountability. Our objective was to determine whether there is an association between industry support and scholarly impact among academic otolaryngologists. Methods: Faculty listings, academic rank, and fellowship training of academic otolaryngologists were accessed from departmental websites. H‐indices, number of publications, and publication range (years) of each individual were calculated using the Scopus database. The Center for Medicare and Medicaid Services Open Payments database was used to determine industry payments during 2014 to each otolaryngologist. Results: Of 1, 515 otolaryngologists, 65.4% received industry support and 15.8% received support > $1, 000. No difference in impact, as measured by the h‐index, was noted upon comparison of those receiving support and those who did not ( P > 0.05). Individuals receiving > $1, 000 had higher h‐indices and total publications than those receiving < $1, 000 or receiving no support (H = 17.8 vs. 10.9, P < 0.0001), even upon controlling for academic seniority. Upon organization by subspecialty, individuals receiving > $1, 000 had greater scholarly impact among most subspecialties. Industry contributions increased with advancing experience. Conclusion: Receiving industry contributions greater than $1, 000 is associated with greater scholarly impact among academic otolaryngologists. In a smaller surgical specialty, such as otolaryngology–head and neck surgery, direct industry research support—as well as indirect contributions through the support of educational programs, consulting, and other expenses—potentially impacts scholarly discourse; these findings do not reflect a causal relationship and may require further characterization. Level of Evidence: NA Laryngoscope, 127:87–94, 2017